A study on association between inguinal hernia and benign prostatic hyperplasia - Parthiban, Suganth Sarvesh; Durairaj, Balaji (International Surgery Journal, 2019)
Background: Inguinal hernia is the most common cause of abdomen wall hernias with multiple etiological risk factors. Benign prostatic hyperplasia (BPH) is the most important cause of bladder outlet obstruction in elderly males leading to chronic straining and difficulty in micturition, which can precipitate inguinal hernia. The occurrence of both inguinal hernia and BPH with lower urinary tract symptoms increases with age. Some studies show that their occurrence together is considered a chance co-existence rather than cause and effect. This study is aimed to find out whether BPH is a significant risk factor for developing inguinal hernia in males. Methods: This study was conducted at a tertiary care hospital in Chennai. 126 males, aged 40 and above were selected according to inclusion criteria and were divided into two groups viz cases (with inguinal hernia) and controls (without inguinal hernia). IPSS scoring chart, prostate volume and uroflometric analysis were done for both groups and results were compared. Results: IPSS scoring showed 22 cases (35%) and 22 controls (35%) had moderate to severe symptoms and no statistical significance. The mean prostate volume in cases was 22.5 g compared with 22.6 g among controls and was statistically insignificant. 11 cases (17%) and 13 controls (21%) had Qmax value less than 15 and the difference was statistically insignificant. Conclusions: This study shows that, although both inguinal hernia and benign prostatic hyperplasia are seen with increased frequency in the aged male population, there is no statistically significant association between the two. Their occurrence together is considered a chance co-existence rather than cause and effect.